Manipulação, Prática Profissional e Deontologia na Fotografia de Informação: primeiros resultados de uma pesquisa em andamento - César Vialle Munhoz, Paulo (Revista Vozes dos Vales: Publicações Acadêmicas, 2015)
This article presents some partial results of ongoing doctoral research in the Postgraduate Program in Communication and Contemporary Culture at the Faculty of Communication of the Federal University of Bahia, under the supervision of Professor Marcos Palacios. It investigates the impacts caused by new digital editing and manipulation technologies on the field of information photography. It seeks to identify benchmarks and indicators that make it possible to assess – in concrete cases of photographic practice – to what extent deontological codes and conventions are being altered as a result of digital image production and processing tools. In a preliminary effort, we sought to assess whether the rules of photography contests were delineating boundaries between what has been stigmatized as "manipulation" of content and what would characterize only a "technical adjustment" of the image. The photography contests were considered valid indicators of the limits of such boundaries, as they represent an institutionalized space for the field's own components to showcase the excellence of their products. The initial results indicate that a large part of the rules are limited to generic observations regarding procedures related to photographic editing, often not clearly defining the line that separates technical adjustment from content manipulation. Even so, the contest rules may lead to the identification of possible regularities that would function as ethical parameters in relation to the post-production of photographic images.
Keywords: Digital Technologies; Digital Photography; Image Manipulation; Information Photography; Deontology